Case studies of some selected rural enterprise projects in Kishoreganj: a tentative financial analysis - Matin, Rukhsana (BRAC, 2019)
This study aimed to assess the viability of eight small scale potential economic enterprises covering the production of sweet toy, rubber shoe, toothpowder, ball pen candle, plastic bag, spice packet and rice mill introduced in 1998 by BRAC's Rural Enterprise Project (REP) from both the organization and members' perspectives, using ratio analysis. The paper reveals that majority of the enterprises discussed have the potential to contribute significantly to higher rural incomes. However all these projects are not homogenous and some are more productive than others. Findings indicate that member involved in the making of candles earn the highest gross profit followed by plastic bag and ball pen. Rice mill, toothpowder and sweet toy have also been found to be quite promising. Comparing the return on investment, with the exception of rubber shoe and spice packets, all projects are more or less viable. Many factors could be held responsible for the losses incurred in the making of rubber shoe and spice packets. For a firm to grow successfully, appropriate techniques of production must be chosen to ensure that these are in accordance with the local factor endowments.